Pandangan K.H. Hasyim Asy’ari terhadap Adab Seorang Ilmuwan dan Relevansinya di Era Digital - Paramansyah, Arman; Muhyidin, Muhammad (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research analyzes and describes the views of K.H. Hasyim Asy'ari on the Manners of a Scientist and Their Relevance in the Digital Era, as a central figure in various areas of national needs, the kyai and nobles who are inherent in him do not become shackles to forming a personality with far-reaching effects. This research uses library research with a qualitative approach. The results of this research show that the etiquette of a scientist in the book “Ādabul 'Ālim wal Muta'allim” contains a concept of etiquette that is appropriate for a scientist and of course the effect is on society globally. Adab or a good personality, he had a concept for purposes that are not momentary so that the theories in his thinking are relevant at this time, of course by assessing the rapid and rapid turnaround of human civilization today. So the etiquette of a scientist can be a role model with the knowledge he has and be able to become an inspiring intellectual figure in the digital era, especially social media. A scientist must be able to maintain etiquette in expressing his opinions on social media and be able to be a good role model in the midst of the rapid flow of globalization. .